Size and distribution of palladium nanoparticles electrodeposited on graphite - Saldan, I.; Girella, A.; Milanese, C.; Fratini, E.; Dobrovetska, O.; Levchuk, I.; Kuntyi, O. (Functional Materials, 2018)
Morphology and particle size distribution of palladium nanoparticles obtained by pulse electrodeposition on graphite surfaces in dimethylformamide solution containing 0.01 M PdCl₂ were examined by field emission scanning electron microscopy. Chemical composition of the deposits was determined by energy dispersive X-ray spectroscopy. It was found that the average size of palladium nanoparticles increased while their density decreased with the number of pulse cycles.